Website Sistem Pengaduan Pegawai Pada Layanan Departemen IT PT Kereta Api Indonesia (Persero) Divisi Regional III Palembang - Popy Anisah (Institute of Information Technology and Social Science (IITSS), 2021)
The Employee Complaint System Website for the IT Department of PT Kereta Api Indonesia (Persero) Division III Palembang is an innovative platform aimed at facilitating the reporting and resolution of issues related to IT services at PT KAI Division III Palembang. Through this website, employees have easy and quick access to report technical or non-technical issues they encounter in using the company's IT systems. The system is designed to expedite response and resolution to each complaint, enhance operational efficiency, and strengthen the relationship between the IT department and end-users. Thus, this website is expected to improve the overall quality of IT services at PT KAI Division III Palembang.